Optimizing the Implementation of Immigration Supervision on Foreign Investors (Study at the Class I Non-TPI Immigration Office, Central Jakarta) - Muhammad Benaya Yudhistira Fath; Budy Mulyawan; Syakir Syakir (IHSA Institute, 2022)
This study aims to find out what obstacles are faced in the supervision of foreign investors and the countermeasures carried out at the Immigration Office Class I Non TPI Central Jakarta. In this study, the authors used normative and empirical research methods, while the data sources were obtained using primary and secondary data. Data collection techniques were carried out using qualitative methods in the form of literature studies, field observations or observations, and also interviews. The results of the study indicate that there are several obstacles that prevent officers from carrying out immigration control such as legal factors that regulate foreign investors, law enforcement factors related to those carrying out law enforcement, facilities or facilities that should facilitate work, cultural factors of the community in responding to foreigners who commit a violation, and also related to the supervisory factor in data transparency of Foreign Investors.